MP24: Effect on pain of an oral sucrose solution versus placebo in children 1 to 3 months old needing nasopharyngeal aspiration; a randomized controlled trial. (15th May 2017) - Alix-Séguin, L.; Desjardins, M.; Gaucher, N.; Lebel, D.; Gravel, J.; Gouin, S.
Abstract : Introduction: Oral sweet solutions have been accepted as effective pain reducing agents for neonates. However studies in the Emergency Department (ED) setting have conflicting results. The objective is to compare the efficacy of an oral sucrose solution versus placebo in reducing pain in children 1 to 3 months of age during nasopharyngeal aspiration (NPA) in the ED.Methods: A randomized, double-blinded, placebo controlled clinical trial was conducted in a pediatric university-affiliated hospital ED. Participants from 1 to 3 months of age requiring NPA were recruited and randomly allocated to receive 2 mls of an 88% sucrose solution (SUC) or 2 mls of a placebo solution (PLA) orally, 2 mins before NPA. The primary outcome was the mean difference in pain scores at 1 min post NPA as assessed by the Face, Legs, Activity, Cry and Consolability (FLACC) Pain Scale. Secondary outcomes were the difference in pain scores using the Neonatal Infant Pain Scale (NIPS), crying time, heart rate and adverse events.Results: 72 participants were recruited and completed the study, 37 (group SUC) and 35 (group PLA) respectively. Both groups had similar demographic and clinical characteristics and baseline FLACC and NIPS pain scores (all p=value >0.4). The mean difference in FLACC scores compared to baseline was 3.3 (2.5-4.1) (SUC) vs. 3.2 (2.3-4.1) (PLA) (p=.94) at 1 min and -1.2 (-1.7 to 0.7) (SUC) vs. -0.8 (-1.5 to -0.1) (PLA) (p=.66) at 3 mins after NPA. For the NIPS scores, it was 2.3 (1.6-3.0) (SUC) vs. 2.5 (1.8-3.2) (PLA) (p=.86) at 1 min and -1.2 (-1.6 to -0.8) (SUC) vs. -0.8 (-1.3 to 0.2) (PLA) (p=.59) 3 mins after NPA. There was no difference in the mean crying time, 114 (98-130) secs (SUC) vs. 109 (92-126) secs (PLA) (p=.81). No significant difference was found in participants' heart rate at 1 min 174 (154-194) BPM (SUC) vs. 179 (160-198) BPM (PLA) (p=.32) and at 3 mins 165 (143-187) BPM (SUC) vs. 164 (142-186) BPM (PLA) (p=.86) after NPA. Three patients had vomiting during the procedure (2 PLA and 1 SUC), and one had an episode of chocking (PLA).Conclusion: In infants 1 to 3 months of age undergoing nasopharyngeal aspiration in the ED, administration of an oral sweet solution did not statistically decrease pain scores as measured by the FLACC and NIPS scales. Participants' heart rate and crying time were not significantly decreased when sucrose was provided.